Reaction Kinetics and Catalytic Performance of KOH- Modified CaO in Tamanu Oil Biodiesel Production - Sunarti, Aryelvia; Firman Kurniawansyah; Syuaibatul Islamiyah; Elva Febriyanti; Achmad Roasyadi; Muhammad Al Muttaqi; Reva Edra Nugraha (University of Jember, 2026)
Biodiesel development as a renewable energy source continues to advance, reducing dependence on fossil fuels. Biodiesel is produced through esterification and transesterification reactions, aided by a catalyst, to increase the reaction rate. One of the main challenges in biodiesel production is selecting a catalyst that is highly active, stable, and easily separated from the product. Heterogeneous catalysts based on calcium oxide (CaO) are a promising alternative, especially when modified to enhance their catalytic performance. CaO has the weakness that it easily reacts with moist air to form calcium hydroxide (Ca(OH)₂). This process can decrease the catalytic activity of CaO. This research aims to determine the energy required for the transesterification reaction using a KOH-modified CaO catalyst in a batch process. A KOH-modified CaO catalyst was synthesized by calcining chicken eggshells and impregnating them with KOH. It was then used to produce biodiesel from tamanu oil through transesterification in a batch reactor. Characterization of the catalyst using the basicity test method showed a basicity value of 2.98 mmol/g benzoic acid, and using the Brunauer-Emmett-Teller (BET) method, obtained a surface area of 0.273 m²/g. The transesterification process was carried out at a mole ratio of oil to methanol of 1:3 at various temperatures of 55–75 °C and reaction times of 90, 120, and 150 minutes. The biodiesel produced was analyzed for free fatty acid (FFA) content, density, kinematic viscosity, yield, and reaction kinetics. The results showed that the optimum conditions were achieved at 65 °C and a reaction time of 120 minutes, yielding a biodiesel yield of 71.4%, and all quality parameters met the SNI 7182:2015 standard. Kinetic analysis showed that the transesterification reaction followed a zero-order kinetic model with an activation energy of 129.72 J/mol, indicating that the modified CaO catalyst effectively reduces the reaction energy barrier.